Characteristics and hospital course of patients admitted for acute cardiovascular diseases during the coronavirus disease-19 outbreak. Issue 1 (January 2021) - Zorzi, Alessandro; Vio, Riccardo; Rivezzi, Francesco; Falzone, Pasquale V.; Giordani, Andrea S.; Condello, Chiara; Dellino, Carlo M.; Deola, Petra; Gallucci, Marco; Giannattasio, Alessia; Licchelli, Luca; Lupasco, Diana; et al.
Abstract : Introduction: During the coronavirus disease-19 (COVID-19) outbreak in spring 2020, people may have been reluctant to seek medical care fearing infection. We aimed to assess the number, characteristics and in-hospital course of patients admitted for acute cardiovascular diseases during the COVID-19 outbreak. Methods: We enrolled all consecutive patients admitted urgently for acute myocardial infarction, heart failure or arrhythmias from 1 March to 31 May 2020 (outbreak period) and 2019 (control period). We evaluated the time from symptoms onset to presentation, clinical conditions at admission, length of hospitalization, in-hospital medical procedures and outcome. The combined primary end point included in-hospital death for cardiovascular causes, urgent heart transplant or discharge with a ventricular assist device. Results: A similar number of admissions were observed in 2020 ( N  = 210) compared with 2019 ( N  = 207). Baseline characteristics of patients were also similar. In 2020, a significantly higher number of patients presented more than 6 h after symptoms onset (57 versus 38%, P  < 0.001) and with signs of heart failure (33 versus 20%, P  = 0.018), required urgent surgery (13 versus 5%, P  = 0.004) and ventilatory support (26 versus 13%, P  < 0.001). Hospitalization duration was longer in 2020 (median 10 versus 8 days, P  = 0.03). The primary end point was met by 19 (9.0%) patients in 2020 versus 10 (4.8%) in 2019 ( P  = 0.09). Conclusion: Despite the similar number and types of unplanned admissions for acute cardiac conditions during the 2020 COVID-19 outbreak compared with the same period in 2019, we observed a higher number of patients presenting late after symptoms onset as well as longer and more complicated clinical courses.